Navigating emotion in HR work: caring for ourselves?. Issue 6 (2nd September 2019) - Rivers, Elizabeth
Abstract : Purpose: The purpose of this paper is to understand how human resource (HR) practitioners subjectively experience emotions in their working lives and how they navigate emotionally challenging work. Design/methodology/approach: A narrative methodology and participant-led photo-elicitation methods were used with five HR practitioners from different sectors to uncover experiences of emotion in their work. Findings: Participants describe themselves as perceived by non-HR employees as non-emotional human beings, expected to "take" emotional expression from others, but to display little themselves. HR practitioners use emotion-focussed coping strategies, both self and team-care, to cope with the emotionally challenging work inherent in their role. Research limitations/implications: As a pilot study of five participants, further research is needed to strengthen the findings; however, the in-depth qualitative methods used provide rich insight into their working lives. Practical implications: HR practitioners' well-being should not be taken for granted or overlooked in organisations. Opportunities for informal networking with HR communities and training/coaching interventions could provide support on approaches to the emotional challenges faced. Originality/value: This paper provides insights into how HR practitioners experience the challenges of their work, in contrast to mainstream research emphasising the impact of human resource management policy and practices on employees and organisations. Attention is drawn to the subjective experience of emotion, rather than the mainstream objectification, managerialisation and generalisation of emotion.